Characterization of the gut microbiome of hooded seals (Cystophora cristata) - Acquarone, Mario; Salgado, Alejandro Flores; Sundset, Monica Alterskjær (2016)
Poster from 30th Conference of the European Cetacean Society. Arranged in Funchal, Madeira, from 14.03.16 - 16.03.16.